The design principles of Al-Mahdi Karaj Street sidewalk with vitality approach - Sedigheh Moein Mehr; Arefe Tamizi (طراحی و برنامه ریزی در معماری و شهرسازی)
In recent decades, with the excessive expansion of cities, the role of pedestrians in the streets has diminished, which has created dull environments in cities and reduced the vitality of urban spaces. Sidewalks are one of the most important urban spaces for spending time due to their special functional, social and cultural role. are leisure and social activities. The purpose of this research is to explain the design principles of Al-Mahdi Street sidewalk to promote social interaction and increase vitality for interaction between citizens. Al-Mahdi Street, which is one of the busiest streets in Karaj city, has become a place for peddlers if it is pedestrian-oriented. The research method of this research is qualitative research which is collected through library studies and field observations in a descriptive-analytical way. This article shows the importance of integrating the principles presented in this research with the needs and culture of Karaj neighborhood to create an inviting and lively atmosphere. This study confirms that attention to the smallest details in design can have profound effects on the mood and behavior of citizens and turn any urban space into a platform for enriching social life and urban sustainability.In recent decades, with the excessive expansion of cities, the role of pedestrians in the streets has diminished, which has created dull environments in cities and reduced the vitality of urban spaces. Sidewalks are one of the most important urban spaces for spending time due to their special functional, social and cultural role. are leisure and social activities.